Affective and cognitive reactivity to mood induction in chronic depression - Guhn, Anne; Sterzer, Philipp; Haack, Friderike H.; Köhler, Stephan (Journal of affective disorders, 2018)
Chronic depression (CD) is strongly associated with childhood maltreatment, which has been proposed to lead to inefficient coping styles that are characterized by abnormal affective responsiveness and dysfunctional cognitive attitudes. However, while this notion forms an important basis for psychotherapeutic strategies in the treatment of CD, there is still little direct empirical evidence for a role of altered affective and cognitive reactivity in CD. The present study therefore experimentally investigated affective and cognitive reactivity to two forms of negative mood induction in CD patients versus a healthy control sample (HC). For the general mood induction procedure, a combination of sad pictures and sad music was used, while for individualized mood induction, negative mood was induced by individualized scripts with autobiographical content. Both experiments included n = 15 CD patients versus n = 15 HC, respectively. Interactions between affective or cognitive reactivity and group were analyzed by repeated measurements ANOVAs. General mood induction neither revealed affective nor cognitive reactivity in the patient group while the control group reported the expected decrease of positive affect [interaction (IA) affective reactivity x group: p = .011, cognitive reactivity x group: n.s.]. In contrast, individualized mood induction specifically increased affective reactivity (IA: p = .037) as well as the amount of dysfunctional cognitions in patients versus controls (IA: p = .014). The experiments were not balanced in a crossover design, causal conclusions are thus limited. Additionally, the differences to non-chronic forms of depression are still outstanding. The results suggest that in patients with CD, specific emotional activation through autobiographical memories is a key factor in dysfunctional coping styles. Psychotherapeutic interventions aimed at modifying affective and cognitive reactivity are thus of high relevance in the treatment of CD. •Altered reactivity to emotional distress is assumed to play a key role in CD.•However, general mood induction did not reveal reactivity in CD.•Individualized mood induction did reveal affective and cognitive reactivity in CD.•Reactivity in CD thus depends on individual relevance.•Psychotherapeutic tools are needed that decrease reactivity to memory activation.